First Record of Black Widow Spider Bite Latrodectus cinctus (Araneae: Theridiidae) From Iran. Issue 3 (4th March 2022) - Nejati, Jalil; Bueno-Marí, Rubén; Salehi, Masoud; Akbari, Mohammad Reza; Shahi, Mehran
Abstract: The genus Latrodectus contains the most medically important spiders around the world. This study describes the first case of Latrodectus cinctus Blackwall, 1865 bite and clinical treatment from Iran. Also, it is the first collection report from the southeast of the country that can enhance prior knowledge on the geographical distribution of this species. We describe a 42-year-old female patient with neurological pain caused by the spider bite. Also, a summary of the entomological survey and morphological identification of the collected species from the patient's house is presented.